"Living" luminogens: light driven ACQ-to-AIE transformation accompanied with solid-state actuation. Issue 6 (1st April 2020) - Wang, Haoran; Xing, Hao; Gong, Junyi; Zhang, Haoke; Zhang, Jun; Wei, Peifa; Yang, Guojian; Lam, Jacky W. Y.; Lu, Ran; Tang, Ben Zhong
Abstract : In situ ACQ-to-AIE transformation was achieved by light-induced [2+2] cycloaddition via through-space conjugation. Abstract : In situ photo-irradiation of trans -2-(4-fluorostyryl)benzo[ d ]oxazole ( t -FSBO) and trans -2-(2, 4-difluorostyryl)benzo[ d ]oxazole ( t -2FSBO) with aggregation-caused quenching (ACQ) characteristics in the solid-state afforded unprecedented aggregation-induced emission (AIE) luminogens through [2+2] cycloaddition. Although the photoreaction products were weakly conjugated, they were emissive. Interestingly, the product cisoid -2, 2′-(3, 4-bis(2, 4-fluorophenyl)cyclobutene-1, 2-diyl)bis(benzo[ d ]oxazole) ( c -2FPCBO) could form blue and yellow emissive crystals due to the different packing modes. Crystallographic results and computational calculation suggested that this anomalous phenomenon was attributed to intramolecular and intermolecular through-space conjugation. To the best of our knowledge, this is the first reported in situ ACQ-to-AIE transformation achieved by UV irradiation, deepening the understanding that non-conjugated molecules can be emissive. In addition to this novel and accessible ACQ-to-AIE transformation, the photosalient effect was also observed during the reactions. Notably, a macroscopic actuator was achieved by simply coating t -FSBO on a nitrile butadiene glove, which could bend over 70° towards UV light source. This system thus offers a new class of AIE luminogens with a "living" character.